Words that start with B - VanSickle, Vikki (Scholastic Canada, 2010)
Grade seven was supposed to be the best ever, but so far things are not turning out so well for Clarissa. It is hard enough being the unexceptional duaghter of a beauty queen, but lately her best freind Benji can seem to stand up for himself and Michael keeps giving her strange gifts. When Mattie, a world-class goodie-two-shoes seems to think they are best freinds, can things possibly get worse--of course they can